1997
DOI: 10.1017/s003329179700562x
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity in cognitive functioning of schizophrenic patients evaluated by a lexical decision task

Abstract: This finding provides evidence for the cognitive heterogeneity of schizophrenic subjects. This absence of priming effect in thought-disordered schizophrenic subjects supports the hypothesis that these patients present a deficit in the post-lexical controlled information processing that permits the integration of semantic information.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
1

Year Published

2002
2002
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(33 citation statements)
references
References 24 publications
1
31
1
Order By: Relevance
“…A French research group, in two LDT studies with similar conditions, has found TD participants unable as a group to demonstrate a significant semantic priming effect, in contrast to non-TD schizophrenia participants, psychiatric controls or normal controls Passerieux et al, 1997). In these studies the SOA was 500 ms and relatedness proportion was 50% (though in Passerieux et al they indicate that the "proportion of related prime-target pairs was 16.7%," this figure appears to be the proportion of total pairs of letter strings, i.e., including pairs with nonwords, that are related word pairs).…”
Section: Evidence For Impaired Controlled/ Attentional Information Prmentioning
confidence: 99%
See 3 more Smart Citations
“…A French research group, in two LDT studies with similar conditions, has found TD participants unable as a group to demonstrate a significant semantic priming effect, in contrast to non-TD schizophrenia participants, psychiatric controls or normal controls Passerieux et al, 1997). In these studies the SOA was 500 ms and relatedness proportion was 50% (though in Passerieux et al they indicate that the "proportion of related prime-target pairs was 16.7%," this figure appears to be the proportion of total pairs of letter strings, i.e., including pairs with nonwords, that are related word pairs).…”
Section: Evidence For Impaired Controlled/ Attentional Information Prmentioning
confidence: 99%
“…TD schizophrenia groups have been found to demonstrate enhanced semantic priming (Henik et al, 1995;Manschreck et al, 1988;Spitzer et al, 1993a;1993b;Weisbrod et al, 1998), semantic priming comparable to those of non-TD schizophrenia groups or controls (Barch et al, 1996;Blum & Freides, 1995), or reduced semantic priming effects compared to those of non-TD schizophrenia groups or controls Besche et al, 1997;Henik et al, 1992;Passerieux et al, 1997). In addition, Spitzer's group has reported on a non-clinical participant sample among whom high scorers on a scale derived from the language-related complaints of schizophrenia patients showed significantly increased semantic priming compared to the low scorers on this scale (Moritz et al, 1999).…”
Section: Semantic Priming Effects and Clinical Phenomenologymentioning
confidence: 99%
See 2 more Smart Citations
“…The hypothesis of dysfunction in automatic activation within semantic networks assumes that the initial activation is faster acting and/or spreads too far, which results in loose associations and derailed thinking (17)(18)(19)(20). The hypothesis of disturbed controlled processes assumes that semantic dysfunction manifests itself later, when the processes of integrating a prior semantic context come into play (21)(22)(23)(24)(25)(26)(27). This inability to maintain the prior context or task-relevant information could produce speech marked by loose and bizarre associations.…”
Section: Nih-pa Author Manuscriptmentioning
confidence: 99%